INFLUENCE OF EXTRACTION PROCESS ON YIELD, TOTAL PHENOLIC CONTENT, AND ANTIOXIDANT PROPERTIES OF AVOCADO (PERSEA AMERICANA MILL.) OIL AND STABILITY ASSESSMENT - CHAIYASUT, CHAIYAVAT; KESIKA, PERIYANAINA; Sirilun, Sasithorn; Makhamrueang, Netnapa; Peerajan, Sartjin; Sivamaruthi, Bhagavathi Sundaram (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study evaluated the impact of drying and storage conditions on the quality of the avocado oil. Methods: The fresh avocado was obtained from local farmers of Chiang Mai province, Thailand. The avocado pulp was collected and blended. The blended samples were dried at different temperatures (60, 80, and 100°C) and the oil was extracted by manual or mechanical pressing. The avocado oil samples were stored in clear and amber glass bottles at various temperatures (4, 30, and 40°C) for 3 months. The organoleptic, Folin–Ciocalteu colorimetric, 1,1-diphenyl-2-picrylhydrazyl and 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid assay, and titration methods were used to measure the physical changes (color, odor, and precipitation), total phenolic content (TPC), antioxidant activity, and acid value (AV) and peroxide values (PVs) of the samples, respectively. Results: The manual squeezing and mechanical pressing methods yielded about 1.17 and 24.91% of avocado oil from fresh, undried avocado flesh, and the pH of both samples was 5. The AV of manually squeezed and mechanically pressed oil samples was 2.91 and 2.88 mg KOH/g of oil, respectively. The PV of manually squeezed and mechanically pressed oil samples was 7.96 and 8.03 milliequivalent of oxygen per Kg of oil, respectively. The quality of the avocado oil dried at 60°C was high compared to other samples regarding TPC and antioxidant capacity. The storage of oil samples for 3 months at various temperatures and in different containers has not affected the quality significantly, except at 40°C. Conclusion: The study proposed that the drying process at more than 80°C interferes with the quality of the avocado oil, and the storage conditions have a greater impact on the stability of the avocado oil. The storage at a low temperature in the absence of light may extend the shelf life of the avocado oil.